2003
DOI: 10.1034/j.1399-3089.2003.01140.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting gene expression to endothelium in transgenic animals: a comparison of the human ICAM‐2, PECAM‐1 and endoglin promoters

Abstract: It is highly likely that successful pig-to-human xenotransplantation of vascularized organs will require genetic modification of the donor pig, and in particular of donor vascular endothelium. Promoters are generally tested in transgenic mice before generating transgenic pigs. Several promoters have been used to drive endothelial cell-specific expression in mice but none have yet been tested in pigs. We compared the promoters of three human genes that are predominantly expressed in vascular endothelium: interc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…An approximately 750-bp fragment from the promoter region is reported to target variable levels of gene expression to the endothelium of capillaries, but not large vessels in transgenic mice. 27 This, together with the common use of distal regulatory elements to enhance tissue specific gene transcription, 28,29 points to the existence of regions outside the promoter fragment that enhance endogenous endoglin expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An approximately 750-bp fragment from the promoter region is reported to target variable levels of gene expression to the endothelium of capillaries, but not large vessels in transgenic mice. 27 This, together with the common use of distal regulatory elements to enhance tissue specific gene transcription, 28,29 points to the existence of regions outside the promoter fragment that enhance endogenous endoglin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work on the endoglin promoter has revealed that gene transcription is initiated from a stretch of DNA that has neither a TATA nor CAAT consensus sequence. 23,24 This promoter region contains GC-rich regions and consensus motifs for a number of transcription factors including Sp1, Ets, GATA, AP2, nuclear factor B (NFB), and TGF-␤, 27 This, together with the common use of distal regulatory elements to enhance tissue specific gene transcription, 28,29 points to the existence of regions outside the promoter fragment that enhance endogenous endoglin expression.In this study, we used comparative genomics to identify potential regulatory regions of endoglin. We show that conserved Ets binding sites are required for transcriptional activity of the promoter and identify Fli-1, Erg, and Elf-1 as 3 Ets family members that are bound to the promoter in endothelial cells in vivo.…”
mentioning
confidence: 99%
“…However, the same promoter was unpredictable when driving the human A20 gene [19]. A study demonstrated that human intercellular adhesion molecule 2 (ICAM-2) promoter was much weaker in pig than in mice, suggesting that there may be a need for additional regulatory elements to achieve species-specific gene expression in pig [20]. Mouse major histocompatibility complex class I gene H-2K b promoter was used to express human TRAIL (tumor necrosis factor-alpharelated apoptosis-inducing ligand) in transgenic pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Various promoter sequences (ESS) were defined, responsible for endothelial-specific expression of these genes. However, as in the case of shear stress regulation, often more than one element was defined as an ESS in a single endogenous promoter, and the contribution of each of these sequences to endothelial specificity in vitro or in vivo (in the embryo or adult animals) has not been determined [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%